Інтерсеміотичні особливості письмової комунікації - Семенюк, Тетяна Петрівна; Semeniuk, Tetiana P. (Волинський національний університет імені Лесі Українки, 2012)
У статті розглядається поняття комунікації в руслі семіотики, взаємодія знаків різних систем у письмовій комунікації, що породжує утворення семіотично ускладеного тексту.This article deals with the investigation of the notion communication within the semiotics. Great attention is also paid to the interaction of different systems of signs in written communication. The combination of various signs within one text creates the semiotically complicated text.
Intersemiotic Peculiarities of Written Communication
Keywords: комунікація; знак; знакова система; інтерсеміотичність; письмове спілкування; вербальні; невербальні та паравербальні компоненти комунікації; монокодовий; двокодовий (креолізований) та полікодовий текст; communication; sign; sign system; intersemiotics; written communication; verbal; non-verbal and para-verbal means of communication; monocode; decode (creolized) and polycode text